Respiratory measurements and airway clearance device prescription over one year in amyotrophic lateral sclerosis. Issue 1 (2nd January 2020) - Tattersall, R.; Murray, D.; Heverin, M; Rooney, J.; Tobin, K.; Vance, R.; Hardiman, O.; Meldrum, D.
Abstract: Objective: The rates of decline in respiratory measurements, including Peak Cough Flow (PCF) have not been established in Amyotrophic Lateral Sclerosis (ALS). Additionally, optimal prescription of cough adjuncts which aim to increase cough strength are unknown. The primary aim of this study was to quantify declines in respiratory function in ALS using PCF, Sniff Nasal Inspiratory Pressure (SNIP) and Slow Vital Capacity (SVC). Secondary aims were to measure respiratory morbidity, audit the characteristics of those prescribed cough adjuncts, and compare outcomes between treated and untreated cohorts. Methods: A prospective, longitudinal, observational, cohort study evaluated respiratory measures, morbidity, and physical function in ALS patients at three monthly intervals, over one year. Patient and disease characteristics of those prescribed cough adjuncts were profiled at the time of device prescription. Results: one hundred and eight participants with mean age 62.1 ± 11.5 years participated. PCF declined rapidly at a rate of 124.8L/min/year ( p  < 0.001). SNIP, SVC (%predicted), and ALSFRS-R also declined significantly at rates of 18.72cmH2 O, 17.49%, and 9.62 units per year respectively ( p  < 0.001). Thirty-two (29.6%) patients reported 56 incidences of chest infection and 21 died. Patients prescribed a cough adjunct (44.4%) had significantly lower average PCF, SNIP, SVC percent predicted, and ALSFRS-R ( p  < 0.001). Conclusions: This study identified a rapid rate of decline in PCF, a similar decline in SNIP, and slower declines in SVC and ALSFRS-R. Cough adjunct prescription was triggered by declining respiratory measures and recommended PCF thresholds, but also by respiratory symptoms. Chest infections were common in patients regardless of cough adjunct prescription and should be closely monitored.